Initial conditions for hydrodynamics from kinetic theory equilibration - Kurkela, Aleksi; Mazeliauskas, Aleksas (Nuclear physics. A, Nuclear and hadronic physics, 2017)
We use effective kinetic theory to study the pre-equilibrium dynamics in heavy-ion collisions. We describe the evolution of linearized energy perturbations on top of out-of-equilibrium background to the energy-momentum tensor at a time when hydrodynamics becomes applicable. We apply this description to IP-Glasma initial conditions and find an overall smooth transition to hydrodynamics. In a phenomenologically favorable range of η/s values, early time dynamics can be accurately described in terms of a few functions of a scaled time variable τT/(η/s). Our framework can be readily applied to other initial state models to provide the pre-equilibrium dynamics of the energy momentum tensor.